Marketing on Instagram Towards Purchase Intention, Mediating Role of Brand Awareness and E-WOM: Evidence from Indonesia’s Bottle Water - Widiasti Fauzia, Hamas; Permana, Dudi (Dinasti International Journal of Management Science, 2024)
The bottled water industry has experienced rapid growth in recent decades, driven by increasing awareness of the importance of safe and healthy drinking water. With intensifying competition, companies in this industry must continuously innovate their marketing strategies to attract and retain customers. In this context, social media has become an essential tool for reaching consumers and influencing their purchasing decisions. This study aims to identify the impact of social media marketing on purchase intention in the bottled water industry, mediated by brand awareness and e-WOM. The research employs a quantitative method based on statistical information. The population in this study consists of consumers who have purchased bottled water products in the last three months, with a total sample of 200 respondents selected using purposive sampling technique. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that social media marketing has a positive and significant effect on brand awareness, e-WOM, and purchase intention. Brand awareness and e-WOM positively and significantly influence purchase intention. Moreover, social media marketing positively and significantly impacts purchase intention through brand awareness or e-WOM as mediating variables on Instagram for bottled water.